#TITLE_ALTERNATIVE# - (NIM 20500005), WIJOYO
Separation process with membrane has a lot of advantages compared to conventional separation process. However, the use of this technology in Indonesia still has many constraints such as the limitation of polymers that have to be imported. The purpose of this research is to look for the alternatives of membrane materials by exploring the use of natural resources in Indonesia such as wood. Cellulose acetate membrane was prepared from Eucalyptus alha pulp by using phase inversion method, with a composition of 17% weight cellulose acetate, 27% weight formamide and 56% weight acetone and coagulation in ice water. The resulting membrane has been compared to commercial product and characterized by infrared spectroscopy, acetyl content, relative molecular mass, X-ray diffraction, membrane performance, morphology and mechanical properties. Infrared spectrum showed that the specific absorption from cellulose acetate was observed at 1238,2 cm -1. The result of the acetylation indicates that the acetyl content of cellulose acetate and commercial one were 38,17% and 40,22% respectively. The X-ray diffraction analysis showed that cellulose acetate has amorphous structure, having the degree of crystallinity fort cellulose acetate and commercial one of 20,15 % and 21,19 % respectively. Membrane performances were characterized by dextran T-10, T-40, T-70, T-500 and T-2000. In addition results showed that membrane commercial cellulose. acetate has a rejection coefficient higher than 90% for each dextran. On the other hand, cellulose acetate membrane has a rejection coefficient higher than 90% only for dextran T-40 to dextran T-2000. This data is supported by morphology analysis, which showed that the pore of commercial cellulose acetate closer than cellulose acetate one. All the data showed that cellulose acetate membrane has similar performance as commercial one.